Adherence by nursing professionals to standard precautions in the COVID-19 pandemic - Daniella Corrêa Cordeiro; Jéssica Fernanda Corrêa Cordeiro; Tatiana Areas da Cruz; Guilherme Schneider; Denise de Andrade; André Pereira dos Santos (Universidade Estadual de Maringá, 2023)
It aimed to identify adherence to standard precautions by nursing professionals working in assistance during the COVID-19 pandemic. This is a pilot study with a cross-sectional design. The sample consisted of 169 nursing professionals. As for adherence to standard precautions, 157 (92.9%) participants claim to perform hand hygiene between care intervals. Regarding the use of gloves, most responded that they always wear them. The procedure that had the lowest adherence to standard precautions was intramuscular or subcutaneous injection (93/55%). The chi-square test (X²) indicated that there was no association with educational level, nature of the work institution, nor length of work as a nursing professional. It was concluded that adherence to standard precautions was below the recommended ideal.